Forestry and agriculture policy governance regarding water contestation in State Production Forest (Case of Margo and Ngiyom spring water in Begal forest, Ngawi Regency) - Istyaningrum, Anna (Universitas Muhammadiyah Ponorogo, 2018)
Water related problem usually involving many stakeholder with different interest, attitude, power scale and level, which make it complex as well asÂ water contestation problem in Begal State production forestÂ in Ngawi Regency which involving different level government agency and its community base institution. Teak production forest and rice agriculture area usually located nearby especially in Ngawi regency with 40% agriculture area and 32% forest area, which make high occurrence of water related problem. This research purpose is to identify and analyze the root of water contestation among involved stakeholder in Ngiyom and Margo spring water utilization and its leading factors.Â In depth interview was done to all involved stakeholder in February 2017 to obtain the data about the water contestation problem in this area. Although changes in water and forest land utilization are causing water contestation problem but understanding root of water problem in this research from agriculture and forestry policy are important to make a sustainable solution. Forestry and agriculture governance are use to understand the relation among stakeholder toward water contestation in this area. Social ecological system framework that captures the relation among resource users and governance to resources utilization is useful to get the whole picture of water contestation problem in this area. Government policy on rice agriculture and forestry sector was indirectly affecting the water contestation problem in this area. Combined with in field governance, government policy effect were causing social and economic gap among water resources user in this area.